Community Perception on The Performance of Reak Art Creations - Nuraini Maulandari (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2022)
This study aims to determine the maintenance pattern of Reak artistic creations and the factors behind different community perceptions in Bumi Langgeng Housing, Cimekar Village, Cileunyi District, Bandung Regency, because it is in line with the times. The pattern of maintenance of Reak art creations has changed, as well as changes in lifestyle, increased activity, and ignorance have caused the community to have different perceptions of the staging of Reak art creations. The method used in this research is the descriptive method. Where data was collected through observation and in-depth interviews with community leaders in Bumi Langgeng housing with the technique of determining informants through purposive sampling, namely a sampling technique with certain considerations, the method of taking information was based on informants who knew Reak artistic creations and community leaders in Bumi Langgeng Housing. The research results show that along with the times, Reak art creations in Cimekar Village have started to experience obstacles in their development. In addition, there are two different perceptions of the staging of Reak art creations, namely negative and positive perceptions. Negative perceptions caused by the presence of migrants in Cimekar Village, especially in Bumi Langgeng housing, lifestyle changes and increased activity, and the growing sense of boredom towards Reak art creations that are felt by the community members, so that this allows them not to participate in preserving the creations. Reak art. Positive perceptions caused by people who love, uphold cultural values and understand Reak artistic creations.